Pengaruh Lingkungan Kerja, Budaya Organisasi dan Kepemimpinan Terhadap Kinerja Pegawai Kantor Kecamatan Sanga Desa Kabupaten Musi Banyuasin - Musyodik Musyodik; Omar Hendro; Trisniarty Adjeng Moelyati (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2021)
The formulation of the problem in this study is how the influence of the work environment on employee performance, organizational culture on employee performance, leadership on employee performance and work environment, organizational culture and leadership on employee performance at the Sanga Desa District office. This research method uses descriptive and inferential statistical analysis, with multiple linear regression models. Statistical calculations, resulting in a regression equation Y = 0.275 + 0.141X1 + 0.239X2 + 0.311X3. The results of the study answered the problem formulation which is also the purpose of this study. First, the work environment, organizational culture and leadership together have a positive and significant effect on the performance of the employees of the Sanga Desa, Musi Banyuasin District office. Second, the work environment has a positive and significant effect on the performance of the employees of the Sanga Village office, Musi Banyuasin Regency. Third, organizational culture has a positive and significant effect on the performance of the employees of the Sanga Village office, Musi Banyuasin Regency. Fourth, leadership has a positive and significant effect on the performance of the office employees of Sanga Village, Musi Banyuasin District.Through regression analysis, it is concluded that culture and leadership are more dominant in performance than the work environment of employees. However, leadership is more dominant than the variables of work environment and organizational culture on employee performance. Good leadership, management will be effective in its implementation so that it has an impact on the performance of the employees of the Sanga Village office, Musi Banyuasin District. Researchers provide recommendations, first, employees must provide good service to the community. Second, employees must be able to work together to achieve job goals. Third, leadership. running good work standards and there must be training for employees. Fourth, means to improve the internet / intranet network signal used for recording e-KTP and online village entry and reporting. Fifth, competence to maintain open deliberations. Emphasized to employees in completing tasks and responsibilities must be in accordance with existing work procedures